2018
DOI: 10.1108/imefm-03-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

The effects of board attributes on Sukuk rating

Abstract: Purpose The purpose of this paper is to investigate the effect of board attributes on Sukuk rating in firms listed in Bursa Malaysia (Malaysian Stock Exchange) during the period of 2008 to 2013. Design/methodology/approach This study uses ordinal logit regression model to examine the influence of board attributes (CEO-chairman duality, board size and board independence) on the dependent variable (RATING). Findings The findings of this paper generally support the agency theory and stakeholder theory. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
(82 reference statements)
0
12
1
1
Order By: Relevance
“…Borhan and Ahmad (2018) investigated the determinants of Sukuk ratings while Alam Choudhury and Nurul Alam (2013) presented a new theoretical concept of corporate governance form the Islamic perspective contrary to the conventional governance viewpoint and showed that a new theoretical viewpoint could be used as an alternative to the conventional governance framework. Elhaj et al (2018) investigated the impact of board characteristics on the Sukuk ratings and found that board size, independence and chief executive officer (CEO) duality help to increase Sukuk ratings. All these studies analyzed either the mutual fund star ratings or its impact on the fund performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Borhan and Ahmad (2018) investigated the determinants of Sukuk ratings while Alam Choudhury and Nurul Alam (2013) presented a new theoretical concept of corporate governance form the Islamic perspective contrary to the conventional governance viewpoint and showed that a new theoretical viewpoint could be used as an alternative to the conventional governance framework. Elhaj et al (2018) investigated the impact of board characteristics on the Sukuk ratings and found that board size, independence and chief executive officer (CEO) duality help to increase Sukuk ratings. All these studies analyzed either the mutual fund star ratings or its impact on the fund performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CEO duality occurs when the roles of CEO and chairman are in the hands of the same person. Although some papers do not find any significant effect, overall there seems to be a consensus on the positive relationship between CEO duality and credit risk for countries with widely held ownership, such as Canada, U.S. and U.K., and Asian countries, with the exception of Elhaj et al (2018), who find a negative effect. These results are in line with the agency theory perspective, where reductions in monitoring (Chen and Al-Najjar, 2012) and excessive power concentrated in one person who can expropriate other shareholders (Lewellyn and Muller-Kahle, 2012), increase the firm's credit risk.…”
Section: Ceo Dualitymentioning
confidence: 90%
“…In the North American and U.K. context, most papers find a reducing effect on credit risk with larger boards (Ames et al, 2018;Benson et al, 2018;Fields et al, 2012;Lu and Boateng, 2018;Upadhyay, 2015) as opposed to the finding by Mili and Abid (2016) and Switzer et al (2018b). Results are more mixed in the Asian context, where some authors observe a positive effect (Chiang et al, 2015;Yen et al, 2015) and others a negative effect (Elhaj et al, 2018;7 Most of these studies that analyse the relationship between credit risk and board composition include board independence (24 papers), size (21 papers) and CEO duality (13 papers) significantly more than other board characteristics. Few papers analyse the association between credit risk and foreign directors (5 papers), female directors (4 papers), political connections and board or CEO networks (4 papers), director tenure and managerial ability (4 papers), and CEO power (3 papers).…”
Section: Board Sizementioning
confidence: 98%
“…Their results show that a guaranteed Musharakah Sukuk issued by a highly profitable firm has a higher likelihood to receive a AAA rating and that firm size is not a significant determinant of Sukuk ratings. In the same vein, Elhaj et al (2017) studied the effects of board attributes on Sukuk rating. The evidence shows that Sukuk rating is positively related to CEO-chairman duality, board independence and board size, but negatively associated with firm leverage.…”
Section: Brief Literature Reviewmentioning
confidence: 99%